Perbandingan antara pengaruh pelatihan rehaencalina-rehaencalina-torso (RRT) dan rehaencalina-bench press-torso (RBT) terhadap kemampuan melempar lembing - Atssam Mappanyukki, Andi; Sumaryanto, Sumaryanto; Setyo Kriwanto, Erwin; Mappaompo, M. Adam; Purwanto, Didik (Universitas Nusantara PGRI Kediri, 2023)
Explosive power athletes are a significant requirement in javelin throwing. Increasing the explosive power of the arm requires proper training, including using rehaencalina exercises. This study aimed to determine the modification of rehaencalina exercises to improve the ability to throw javelins. This research uses the Experiment method, which uses a two-group pretest-posttest design. The sample in this study was 18 javelin throw athletes from Makassar State University. The research instrument used a javelin-throwing ability test. Data analysis was processed using descriptive test statistics, normality test, homogeneity test, and Anakova test. The results found a comparison of the effects of the two treatment groups on the variable javelin throwing ability, resulting in an average javelin throwing ability between exercises showing an increase in javelin throwing ability seen from the average increase in test results. The average javelin throwing ability for both groups showed that group 1 of the Rehaencalina-Rehaencalina-Torso (R-R-T) exercise resulted in a better improvement in javelin throwing ability than group 2 of the Rehanecalina-Bench Press-Torso (R-B-T) exercise. This study concludes that arm power explosiveness modification exercises with Rehaencalina exercises can improve javelin throwing ability. The results of this study can be a foothold to pay attention to the physical component in improving sports skills.